Development and Demonstration of Membrane to Control Potential Pathogen (Legionella sp.) Associated With Cooling Towers - Sharma, Neha; Lavania, Meeta; Lal, Banwari (Frontiers in Environmental Science, 2020)
The presence of pathogens in industrial cooling towers has been identified as one of the causes of legionellosis, but the tangible hazard has been unrecognized. The major function of a cooling tower in the industries is to transfer heat into the environment through evaporation which leads to an unusual increment in the conductivity of water. Conductivity indicates dissolved solids of water which further facilitate the occurrence of corrosion within the cooling tower systems that may hamper the overall functioning of the cooling tower. The lab-scale study was conducted to developed and demonstrated an efficient membrane to control potential pathogen (Legionella sp.) associated with cooling tower water. In the present study, cooling tower water from various locations was collected and examined for physicochemical parameters (pH, conductivity, salinity, sulfate, and APS reductase) and microbial load. The phylogenetic analysis of the potential sample (with a maximum load of bacterial counts, P1) confirms the presence of Legionella sp., Pseudomonas sp., and Flavobacterium sp. In the present investigation, a unique membrane was developed to regulate the growth of pathogenic contaminants along with sulfate, alkalinity in the cooling tower water. The membrane was capable of reducing conductivity from 6.03 to 4.5 mS/cm and total microbial load reduced by 40% by passing through the liquid. The developed membrane was characterized through FTIR that indicated the presence of carbonyl, C–CH3 and C–O–C group whereas, thermal properties of the membrane was determined through TGA. Thus the developed membrane may be used for environmental monitoring and maintenance, including anti-scale treatment, and physical, chemical, and microbiological control, ensure the good performance of reducing the Legionella sp. risk for public health in cooling tower stations.